2008
DOI: 10.1159/000129686
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Hydrogen Sulfide Inhibits Superoxide Formation, NOX-1 Expression and Rac<sub>1</sub> Activity in Human Vascular Smooth Muscle Cells

Abstract: The activity of NADPH oxidase (NOX) is blocked by nitric oxide (NO). Hydrogen sulfide (H2S) is also produced by blood vessels. It is reasonable to suggest that H2S may have similar actions to NO on NOX. In order to test this hypothesis, the effect of sodium hydrosulfide (NaHS) on O2 formation, the expression of NOX-1 (a catalytic subunit of NOX) and Rac1 activity (essential for full NOX activity) in isolated vascular smooth muscle cells (hVSMCs) was inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 74 publications
1
83
0
1
Order By: Relevance
“…12 On the basis of these findings, it can be proposed that the increased superoxide dismutase activity would scavenge the superoxide anions in the vessel walls thereby increasing the bioavailability of NO causing preglomerular arteriolar vasodilatation. However, superoxide anions levels were not measured in the present study so the possibility of direct inhibition of superoxide by NaHS 36 or tempol 37 cannot be ruled out. The increase in creatinine clearance and renal cortical blood perfusion support the view that the combination of NaHS and tempol led to an interaction that resulted in a renal arteriolar vasodilatation and reduced pre-glomerular arteriolar resistance.…”
Section: Discussionmentioning
confidence: 65%
“…12 On the basis of these findings, it can be proposed that the increased superoxide dismutase activity would scavenge the superoxide anions in the vessel walls thereby increasing the bioavailability of NO causing preglomerular arteriolar vasodilatation. However, superoxide anions levels were not measured in the present study so the possibility of direct inhibition of superoxide by NaHS 36 or tempol 37 cannot be ruled out. The increase in creatinine clearance and renal cortical blood perfusion support the view that the combination of NaHS and tempol led to an interaction that resulted in a renal arteriolar vasodilatation and reduced pre-glomerular arteriolar resistance.…”
Section: Discussionmentioning
confidence: 65%
“…Inhibition of 'oxidative stress' by inactivating enzymes or the direct 'scavenging' of the oxidant species would be expected to contribute to the many potential anti-inflammatory effects of H 2 S. In vitro experiments have shown that H 2 S generated from sulfide salts (Na 2 S and NaSH) inhibits cellular damage and intracellular protein oxidation induced by HOCl [77,78], ONOO - [79] and • NO [34,80]. NaSH is also reported to scavenge and/or degrade lipid peroxides [81,82] and inhibit the expression and activity of NAD(P)H oxidase [83,84]. Increased hepatic glutathione (GSH) synthesis and decreased lipid peroxidation are also observed with Na 2 S treatment in a murine hepatic ischemia-reperfusion injury model [85].…”
Section: Antioxidant Activity Of H 2 S?mentioning
confidence: 99%
“…In addition, H 2 S ''scavenges'' proinflammatory oxidants such nitric oxide ( NO), peroxynitrite (ONOO -), hypochlorous acid (HOCl) (25,26), superoxide, and hydrogen peroxide (3,6,15); such effects might be expected to alleviate inflammation. Finally, S-diclofenac (an H 2 S-releasing derivative of the nonsteroidal antiinflammatory drug, diclofenac) exhibits more-pronounced antiinflammatory activity in endotoxic shock (11) and against carrageenan-induced hindpaw edema (18) in the rat than does diclofenac.…”
Section: Introductionmentioning
confidence: 99%